1982
DOI: 10.1063/1.330350
|View full text |Cite
|
Sign up to set email alerts
|

Loss separation measurements for several electrical steels

Abstract: Loss separation measurements were made on regular grain oriented 3% Si steels of four sheet thicknesses, one thickness of high permeability oriented 3% Si steel, two grades of nonoriented Si steel, a low carbon steel, a primary recrystallization oriented low alloy iron sample, and an amorphous metal sample. The Bn dependence of hysteresis loss Ph for all samples except the oriented Si steels was close to n=1.6, in good agreement with the Steinmetz value. All the oriented Si steels had n values close to 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Energy loss components of the material were calculated based on the modelled DHL of Fig 11; the results showed that hysteresis energy loss , classical eddy current energy loss , and excess energy loss components account for 41 %, 24 % and 35 % of the total energy loss, respectively. These results are in compliance with the results reported by other researchers for 3 % SiFe GO steels at magnetizing frequency of 50 Hz and peak flux density of 1.7 T [19], [31][32].…”
Section: Constructing the Dynamic Hysteresis Loop (Dhl)supporting
confidence: 93%
See 1 more Smart Citation
“…Energy loss components of the material were calculated based on the modelled DHL of Fig 11; the results showed that hysteresis energy loss , classical eddy current energy loss , and excess energy loss components account for 41 %, 24 % and 35 % of the total energy loss, respectively. These results are in compliance with the results reported by other researchers for 3 % SiFe GO steels at magnetizing frequency of 50 Hz and peak flux density of 1.7 T [19], [31][32].…”
Section: Constructing the Dynamic Hysteresis Loop (Dhl)supporting
confidence: 93%
“…This is a reliable means to validate the modelling results, specifically the constructed SHL, which is in line with the phenomenology of magnetic hysteresis outlined in section II.Energy loss components of the material were calculated based on the modelled DHL of Fig11; the results showed that hysteresis energy loss , classical eddy current energy loss , and excess energy loss components account for 41 %, 24 % and 35 % of the total energy loss, respectively. These results are in compliance with the results reported by other researchers for 3 % SiFe GO steels at magnetizing frequency of 50 Hz and peak flux density of 1.7 T[19],[31][32].To increase accuracy of the modelling at higher frequencies, a new empirical function with the general form of (9) was defined:…”
supporting
confidence: 86%
“…Iron core losses in grain-oriented (GO) steel, the predominant transformer core material, can be divided into three general categories: static hysteresis (which account for about 40% of the total), classical eddy current (about 20%), and excess losses (about 40%) [17]- [19]. The term excess loss reflects the fact that it is anomalous from the viewpoint of the classical loss theory [20], which is mainly applied to non-oriented ("dynamo") steels used in generators and motors.…”
Section: Hysteresis Modelingmentioning
confidence: 99%
“…Letting (4) The losses per phase vary with time as (5) and their average value is (defined above). Replacing by , by (6) it is possible to integrate to obtain (7) Under the same conditions, consumes . Since and should consume the same core losses for a given voltage , the bracketed expression in (7) is obviously defined above (static conductance)…”
Section: B Identification Of Those Conductances 1) Static Conductancementioning
confidence: 99%